Faktor-Faktor yang Berpengaruh pada Kualitas Audit - Rosdiana, Wawan; Asri Dwija Putri, I G. A.M (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
Problems regarding the low level of audit quality have become the focus of the public in recent years. This is due to the involvement of public accountants in it. This study aims to determine the effect of independence, due professional care and accountability on audit quality. This research was conducted in the Public Accounting Firm in Denpasar, which was registered with IAPI in 2018. The sample was selected using a saturated sample technique. Data was collected through questionnaires to auditors and data analysis techniques used were multiple linear regression. The results of the study with t statistical tests showed that partially independence, due professional care and accountability had a positive and significant effect on audit quality at the Public Accounting Firm in the City of Denpasar. Keywords: Independence, due professional care, accountability